2017
DOI: 10.1089/sur.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Hernia Repair: A Meta-Analysis of Randomized Controlled Trials

Abstract: Mesh reinforcement is recommended for all VH repairs in a clean case (high grade of evidence). Sublay mesh location may result in fewer recurrences and SSIs than onlay or inlay placement, but further study is needed to confirm this hypothesis (moderate grade of evidence).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 46 publications
1
53
0
2
Order By: Relevance
“…Great progress in both primary prevention and results of surgical repair has been accomplished over the past decades. 13,14,32,34,35 Continuous examination by physical examination or imaging is time-consuming and often not feasible. Patient-reported outcomes could provide a feasible and costeffective tool for long-term follow-up, which is essential to assess current practice and the effectivity of new closure techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Great progress in both primary prevention and results of surgical repair has been accomplished over the past decades. 13,14,32,34,35 Continuous examination by physical examination or imaging is time-consuming and often not feasible. Patient-reported outcomes could provide a feasible and costeffective tool for long-term follow-up, which is essential to assess current practice and the effectivity of new closure techniques.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports on the risk of infection in hernia repairs with and without a mesh. Mesh reinforcement can prevent hernia recurrence but is also associated with increased J Microbiol Infect Dis www.jmidonline.org Vol 9, No 2, June 2019 surgical site infection [9]. The ideal location of mesh placement is also debated.…”
Section: Discussionmentioning
confidence: 99%
“…4 Holihan et al, in their meta-analysis, reported that sublay mesh location may result in fewer recurrences. 22 Intraperitoneal space is not safe for placing prolen mesh. However it is not recommended, intraperitoneal mesh placement can be safe with prolen mesh reported by Brandi et al 23 Neither acute nor chronic enterocutaneus fistulas were encountered during follow-up in any of the patients in their study.…”
Section: Discussionmentioning
confidence: 99%